3,4-Methylenedioxy-β-Nitrostyrene Alleviates Dextran Sulfate Sodium–Induced Mouse Colitis by Inhibiting the NLRP3 Inflammasome - Zheng, Juanjuan; Jiang, Zhongxin; Song, Yue; Huang, Shu; Du, Yuzhang; Yang, Xiaobao; Xiao, Yan; Ma, Zhihui; Xu, Dakang; Li, Jing (Frontiers in Pharmacology, 2022)
Inflammatory bowel disease (IBD) has been reported to be associated with the NLRP3 inflammasome activation, therefore inhibiting inflammasome activation could be a new approach to against IBD. Inflammasome inhibitors NLRP3-IN-2, JC124, and 3,4-methylenedioxy-β-nitrostyrene (MNS) were previously reported to exert anti-inflammatory effects in various disease models, but not in the dextran sulfate sodium (DSS)-induced colitis model. Here, we showed that MNS was more efficient in inhibiting the secretion of interleukin-1β (IL-1β) by blocking oligomerization of apoptosis-associated speck-like protein (ASC) than NLRP3-IN-2, JC124. To investigate the protective effects of MNS on enteritis, we administered intragastric MNS to DSS-induced colitis mice. Results demonstrated that MNS attenuated DSS-induced body weight loss, colon length-shortening, and pathological damage. Besides, MNS inhibited the infiltration of macrophages and inflammatory cells, reduced IL-1β and IL-12 p40 pro-inflammatory cytokines, but had no effect on TNF-αand IL-6. Furthermore, we also found that the differentiation of IL-17A+interferon-γ (IFN-γ)+CD4+T cell was decreased in the colon after MNS treatment, which might be mediated by IL-1β, etc cytokines release. Taken together, MNS alleviated DSS-induced intestinal inflammation through inhibiting NLRP3 inflammasome activation, which may function as an effective therapeutic for IBD.